NREN Network Security: A case study of Uganda Christian University ICT Infrastructure - Matsiko, Perez; Kiden, Sarah (My University, 2013)
The long wait for high-speed access to the Internet is finally coming to an end. National Research and Education Networks (NRENs) are being connected to the rest of the world through high-speed fiber optic cables. This paper focuses on NREN security with Uganda Christian University (UCU) as a case study. It discusses how regional and national reseach and education networks will signifiantly lower bandwidth costs for the member institutions. It goes ahead to discuss the initial UCU ICT infrastructure, security practices and implementation, and then suggest recommendations based on lessons learnt and experiences.
Keywords: NREN; 802.1x protocol; PacketFence; OpenLDAP; Network Security